The Stability and Dynamics of Vague Legal Concepts as the Central Core and Periphery of Social Representations1 - Smejkalová Terezie (Studies in Logic, Grammar and Rhetoric)
In a related project, the social representation of public order among legal professionals has been explored by means of semi-structured interviews (Smejkalová et al. 2022). The participants of this research represent public order, inter alia, as a stable safeguard of fundamental social values while recognizing its vagueness and inherent propensity for change. This contradiction between its purpose to provide stability while being subject to social or temporal contexts seems akin to the structural approach to social representations.